The Usual, Racialized, Suspects: The Consequence of Police Contacts with Black and White Youth on Adult Arrest. (31st October 2020) - McGlynn-Wright, Anne; Crutchfield, Robert D; Skinner, Martie L; Haggerty, Kevin P
Abstract: Research on race and policing indicates that Black Americans experience a greater frequency of police contacts, discretionary stops, and police harassment when stops occur. Yet, studies examining the long-term consequences of police contact with young people have not examined whether criminal justice consequences of police contact differ by race. We address this issue by examining whether police encounters with children and adolescents predict arrest in young adulthood and if these effects are the same for Black and White individuals. The paper uses longitudinal survey data from 331 Black and White respondents enrolled in the Seattle Public School District as eighth graders in 2001 and 2002. Our findings indicate that police encounters in childhood increase the risk of arrest in young adulthood for Black but not White respondents. Black respondents who experience contact with the police by the eighth grade have eleven times greater odds of being arrested when they are 20 years old than their White counterparts.